Automated Risk Analysis of Asset and Interest Declarations of Public Officials : A Technical Guide - Kotlyar, Dmytro (World Bank, Washington, DC, 2021)
The technical guide distinguishes the automated risk analysis from the general verification of the AID, which is a comprehensive legal procedure carried out by the staff of the verification agency. The automated risk analysis could be a part of the general verification framework. This technical guide builds on the advisory work conducted by the Stolen Asset Recovery Initiative (StAR) team in different countries that use or contemplate using the automated risk analysis of AIDs and consultations with practitioners from other asset declaration systems that use some automation in their verification processes. The proposals and recommendations are not a reflection of one system’s approach to electronic risk analysis but rather include elements from different systems and build on them. The guide goes beyond describing existing approaches and proposes possiblesolutions that can solve some of the implementation challenges faced by countries. The authors adopted this approach given the limited number of countries that use automatic risk analysis in their verification process now and to allow for sharing the lessons learned from the ongoing work advising countries.